Delta-V and ground metric investigations for responsive satellite formation flying - Yahya, Nor Affendy; Varatharajoo, Renuganth; Harithuddin, A. S. M.; Razoumny, Yury (Elsevier, 2022)
This paper studies a responsive mission involving a dual spacecraft flying formation system. A graphical solution based on the selective dependent variables for acquiring the local and global optimum impulsive velocities is proposed to obtain the minimum orbital transfer velocity changes as well as improving its nadir ground coverage. These studies are conducted using finite thrust of single, dual and three-impulse modes under the condition of unperturbed environment. Based on the obtained results, the relationship between the number of impulses applied and the amount of fuel consumed to retain the leader-follower formation separation is inversely proportional. Whereas, in all cases of the ground metric studies, the formation inclination has shown a dominant influence over other parameters for maximizing the total nadir ground coverage and the swath length.